Non-laparoscopic minimal surgical approach to pyloromyotomy: An experience from a challenged resource setting - Ossama M Zakaria (Wolters Kluwer Medknow Publications, 2016)
Background: The aim of the study is to review the experience with the classic Ramstedt's pyloromyotomy through the RUQ approach and the circumlinear supraumbilical fold approach (circumumbilical [CU]) pyloromyotomy (an approach that combines the ease and safety of the open pyloromyotomy with the advantages of minimal invasiveness). Patients and Methods: A single centre review in a period of 12 years from January 2001 to December 2013 with the institutional ethical committee's approval, evaluating 316 pyloromyotomies based on surgical approach: RUQ (171); and CU (145). Patients' demographics, acid-base/electrolyte status on presentation, mean operative time (MOT), postoperative length of stay (LOS) at hospital, and complications were recorded. Results: Patients demographics, acid − base/electrolyte status on presentation; and MOT were not significantly different. The median LOS was 33 and 30 minutes for CU and RUQ, respectively, with no statistical significant difference between the two groups. One patient in the CU group had a late adhesive bowel obstruction requiring laparotomy and bowel resection. Moreover, wound infection rates did not differ significantly between the two groups (CU 3; and RUQ; 3; P = 0.15). Conclusions: Pyloromyotomy is associated with a low complication rate. Cosmetically, CU is superior to the RUQ approach. Its short learning curve and the feasibility to examine the integrity of the duodenal mucosa intraoperatively may make CU a safer alternative in case of surgeons who are still practicing the RUQ approach in countries with a challenged resource settings.